Real world evidence of improved attention and cognition during physical therapy paired with neuromodulation: a brain vital signs study - Kirby, Eric D.; Jones, Christina B.; Fickling, Shaun D.; Pawlowski, Gabriela; Brodie, Sonia M.; Boyd, Lara A.; Venter, Jan; Moser, Nicholas; Kalsi-Ryan, Sukhvinder; Medvedev, George; D’Arcy, Ryan C. N. (Frontiers in Human Neuroscience, 2023)
Non-invasive neuromodulation using translingual neurostimulation (TLNS) has been shown to advance rehabilitation outcomes, particularly when paired with physical therapy (PT). Together with motor gains, incidental observations of patient-reported observations of incidental improvements in cognitive function have been noted. Both studies in healthy individuals and case reports in clinical populations have linked TLNS to improvements in attention-related cognitive processes. We investigated if the use of combined TLNS/PT would translate to changes in objective neurophysiological cognitive measures in a real-world clinical sample of patients from two separate rehabilitation clinics. Brain vital signs were derived from event-related potentials (ERPs), specifically auditory sensation (N100), basic attention (P300), and cognitive processing (N400). Additional analyses explored the attention-related N200 response given prior evidence of attention effects from TLNS/PT. The real-world patient sample included a diverse clinical group spanning from mild-to-moderate traumatic brain injury (TBI), stroke, Multiple Sclerosis (MS), Parkinson’s Disease (PD), and other neurological conditions. Patient data were also acquired from a standard clinical measure of cognition for comparison. Results showed significant N100 variation between baseline and endpoint following TLNS/PT treatment, with further examination showing condition-specific significant improvements in attention processing (i.e., N100 and N200). Overall, the real-world findings support the concept of neuromodulation-related improvements extending beyond physical therapy to include potential attention benefits for cognitive rehabilitation.